Qualitative Lipschitz to bi-Lipschitz decomposition - Bate David (Analysis and Geometry in Metric Spaces, 2024)
We prove that any Lipschitz map that satisfies a condition inspired by the work of G. David may be decomposed into countably many bi-Lipschitz pieces.